Pendampingan Dan Permainan Kreatif Guna Peningkatan Kemampuan Literasi Numerasi Anak di Panti Asuhan Al Hidayah - Martin, Sri Novia; Yerizon, Yerizon; Sari, Shinta; Nazarlin, Nazarlin; Shalina, Ella Tirta; Sifa, Friska Falah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Based on the results of PISA, the numeracy literacy ability of Indonesian students is very low. Therefore, efforts are needed to improve numeracy literacy both in formal learning institutions such as schools and in non-formal learning institutions such as tutoring and orphanages. One of the orphanages that is used as a place of service is the Al Hidayah Padang Orphanage. There are various limitations in both facilities, infrastructure and experts (teachers) who can guide/accompany children in the dormitory, causing children's numeracy literacy skills to be still relatively low. In addition, motivation to read and learn mathematics needs to be increased again.  Therefore, the service team seeks to help the foster children of the Al Hidayah Padang Orphanage to be able to improve their numeracy literacy skills through mentoring activities and creative games.